Pattern of liver function tests in morbidly obese Saudi patients undergoing bariatric surgery - Ahmad Al Akwaa; Ahmad El Zubier; Mohammed Al Shehri (The Saudi Journal of Gastroenterology, 2011)
Background/Aim: Morbidly obese patients have a high prevalence of fatty liver disease and its serious complications, and high prevalence of abnormal liver function tests (LFT). The LFT can give a clue to the liver damage and correlate with activity. We aim to study the pattern of LFT in morbidly obese Saudi patients undergoing bariatric surgery in Eastern region. Patients and Methods: Medical records of patients undergoing bariatric surgery were reviewed. Demographic data, comorbid conditions, and medications taken were recorded. Intraoperative liver appearance was noted. Patients with alcohol intake or without LFT were excluded. Results: Out of 113 patients, 15 patients were excluded, and of the remaining 98 patients analyzed, 58.2% were females. Mean age was 33.1 ± 8.87 years. Mean body mass index (BMI) was 53.7 ± 1.27 kg/m 2 . Abnormal LFT (alanine aminotransaminase (ALT), aspartate aminotransaminase (AST) alkaline phosphatase (ALK), and Gamma glutamyl transpeptidase (GTT) were observed in 17.3%, with 1.5 to 2 times the upper limit of normal. ALT was most elevated in 12.2%. Abdominal ultrasonography was done in 67 (68.4%) patients, of whom 51 (76%) had fatty liver. Comorbid conditions including diabetes mellitus, hypertension, hyperlipidemia, bronchial asthma, and obstructive sleep apnea were observed in 51 (51.50%) patients, eight of them (16.3%) had abnormal LFT. No intraoperative changes of cirrhosis were observed. Conclusion: The prevalence of abnormal LFT is low in morbidly obese patients from the eastern region of Saudi Arabia. A prospective study with a larger sample and liver biopsy, is needed to clarify the findings.